Whole-Genome Sequence of Salmonella enterica subsp. enterica Serovar Typhimurium Strain UPM 260, Isolated from a Broiler Chicken in Perak, Malaysia - Roslan, Najwa Syahirah (Genome Announc, 2017)
Salmonella enterica subsp. enterica serovar Typhimurium is one of several well-categorized Salmonella serotypes recognized globally. Here, we report the whole-genome sequence of S. Typhimurium strain UPM 260, isolated from a broiler chicken.